GROUPING OF MUNICIPALITIES OF THE REPUBLIC OF SERBIA BASED ON DEVELOPMENT OF SMALL AND MEDIUM AGROBUSINESSES - Popović, Blaženka; Maletić, Radojka (Economics of Agriculture, 2008)
Agriculture is branch of economy of special importance to the economy of the Republic of Serbia since it creates approximately 20% of gross national product and has realistic potentials for increase of production volume and processing of agricultural products. Economical potential of agriculture imposes the need for analysis of small and medium entrepreneurship which should be carrier of future development of agribusiness. Cluster analysis is method to determine how the municipalities in the Republic of Serbia are grouped according to the level of development of small and medium agribusinesses. Also, in this way we get insight into current condition of regional development of this sector as well as possibility for development of least developed municipalities in Serbia.